Toroidal modeling of plasma response to RMP fields for HL-2M. (3rd November 2021) - Hao, G.Z.; Li, C.Y.; Liu, Y.Q.; Chen, H.T.; Wang, S.; Bai, X.; Dong, G.Q.; He, H.D.; Zhao, Y.F.; Miao, Y.T.; Zhou, L.N.; Xu, J.Q.; et al.
Abstract: The plasma response to the n = 1, 2, 4 ( n is the toroidal mode number) resonant magnetic perturbation (RMP) fields, and the consequences on the fast ion confinement, are numerically investigated for a reference high-pressure plasma in HL-2M, by utilizing the linear resistive magnetohydrodynamic code MARS-F (Liu et al 2000 Phys. Plasmas 7 3681). The best coil current configurations, in terms of the coil phasing between the upper and lower rows of coils for controlling type-I edge localized modes (ELMs) in HL-2M, are identified as −130, −30, 180 degrees for the n = 1, 2, 4 fields, respectively, based on the edge peeling-tearing plasma response criterion. The plasma is found to substantially amplify the applied vacuum RMP field with the best coil phasing for the reference HL-2M equilibrium. The overall field amplification factor, defined as the peak-to-peak ratio of the poloidal spectra for the total field perturbation including the plasma response and the vacuum field alone, is about five for all n 's. The amplification, however, does not occur with the worst coil phasing for ELM control. This field amplification due to the high-pressure plasma response, together with the plasma screening of the resonant radial field components in the core region, have several consequences on the fast ion confinement in HL-2M during ELM control with RMP. (i) Three-dimensional fields including the plasma response, and with the best coil phasing, substantially enhance the distortion of fast ion orbits compared to the vacuum field approximation. With the n = 1 RMP, the plasma-response-induced enhancement of the orbit distortion reaches a factor of four when measured in terms of the canonical toroidal angular momentum. (ii) With the best coil phasing, the plasma response widens the stochastic region for the particle orbits on the Poincaré plane. (iii) The orbit islands, including the plasma response, remain as large as the vacuum counterparts in the plasma core where strong screening of the resonant field components occur. All these effects lead to enhanced fast ion transport (and loss) in the high-pressure HL-2M plasma, when the best RMP spectrum is applied to control ELMs.